How ‘place’ matters for addressing the HIV epidemic: evidence from the HPTN 071 (PopART) cluster-randomised controlled trial in Zambia and South Africa - Bond, Virginia (Trials, 2021)
BACKGROUND: In a cluster-randomised trial (CRT) of combination HIV prevention (HPTN 071 (PopART)) in 12 Zambian communities and nine South African communities, carried out from 2012 to 2018, the intervention arm A that offered HIV treatment irrespective of CD4 count did not have a significant impact on population level HIV incidence. Intervention arm B, where HIV incidence was reduced by 30%, followed national guidelines that mid trial (2016) changed from starting HIV treatment according to a CD4 threshold of 500 to universal treatment. Using social science data on the 21 communities, we consider how place (community context) might have influenced the primary outcome result. METHODS: A social science component documented longitudinally the context of trial communities. Data were collected through rapid qualitative assessment, interviews, group discussions and observations. There were a total of 1547 participants and 1127 observations. Using these data, literature and a series of qualitative analysis steps, we identified key community characteristics of relevance to HIV and triangulated these with HIV community level incidence. RESULTS: Two interdependent social factors were relevant to communities’ capability to manage HIV: stability/instability and responsiveness/resistance. Key components of stability were social cohesion; limited social change; a vibrant local economy; better health, education and recreational services; strong institutional presence; established middle-class residents; predictable mobility; and less poverty and crime. Key components of responsiveness were community leadership being open to change, stronger history of HIV initiatives, willingness to take up HIV services, less HIV-related stigma and a supported and enterprising youth population. There was a clear pattern of social factors across arms. Intervention arm A communities were notably more resistant and unstable. Intervention arm B communities were overall more responsive and stable. CONCLUSIONS: In the specific case of the dissonant primary outcome results from the HPTN 071 (PopART) trial, the chance allocation of less stable, less responsive communities to arm A compared to arm B may explain some of the apparently smaller impact of the intervention in arm A. Stability and responsiveness appear to be two key social factors that may be relevant to secular trends in HIV incidence. We advocate for a systematic approach, using these factors as a framework, to community context in CRTs and monitoring HIV prevention efforts. TRIAL REGISTRATION: ClinicalTrials.gov NCT01900977. Registered on July 17, 2013.    SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13063-021-05198-5.